1998
DOI: 10.1126/science.281.5382.1502
|View full text |Cite
|
Sign up to set email alerts
|

Segregation of Transcription and Replication Sites Into Higher Order Domains

Abstract: Microscopy shows that individual sites of DNA replication and transcription of mammalian nuclei segregate into sets of roughly 22 and 16 higher order domains, respectively. Each domain set displayed a distinct network-like appearance, including regions of individual domains and interdigitation of domains between the two networks. These data support a dynamic mosaic model for the higher order arrangement of genomic function inside the cell nuclei.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
198
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(215 citation statements)
references
References 16 publications
16
198
0
Order By: Relevance
“…Altogether, these data suggest that replication and transcription could be functionally and temporally coupled. However, other studies in the nucleus mammalian cells show that replication and transcription sites are separate, although interdigitated (Wei et al, 1998). Considering these findings together with the role of BCL6 in transcriptional control, we also directly address the possible role of BCL6 bodies in RNA synthesis and/or storage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, these data suggest that replication and transcription could be functionally and temporally coupled. However, other studies in the nucleus mammalian cells show that replication and transcription sites are separate, although interdigitated (Wei et al, 1998). Considering these findings together with the role of BCL6 in transcriptional control, we also directly address the possible role of BCL6 bodies in RNA synthesis and/or storage.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggested that BCL6 bodies are associated with replicating DNA and/or that their close vicinity is a nuclear micro-environment prone to support DNA replication, and raised the possibility that they influence the replication foci (RF) assembly, positioning, or activity (Albagli et al, 2000). Moreover, together with the proposed spatial coincidence or close apposition between transcription and replication sites in nucleus (Fakan and Nobis, 1978;Jaunin et al, 1998Jaunin et al, , 2000Wei et al, 1998), these previous data led us here to also compare the localization of BCL6 bodies and RNA.…”
Section: Introductionmentioning
confidence: 97%
“…The architecture of the cell nucleus exerts a regulatory role on a variety of functions, e.g., DNA replication, transcription, and RNA splicing (1)(2)(3)(4)(5). The eukaryotic genome is organized in large-scale chromatin domains occupying functionally distinct nuclear compartments (6,7).…”
mentioning
confidence: 99%
“…This striking complexity is not surprising in view of the involvement of the nuclear matrix with many aspects of nuclear functioning. Recent evidence suggests that the matrix represents the architectural basis that mediates chromosome territory organization (3) and segregates numerous separate transcription and replication sites into still higher-order domains (4). Clearly, the nuclear matrix does not represent merely a distinct set of structural proteins.…”
mentioning
confidence: 99%